Child HIV Exposure and CMV Seroprevalence in Botswana: No Associations With 24-Month Growth and Neurodevelopment. (22nd August 2020) - Moraka, Natasha O; Moyo, Sikhulile; Smith, Christiana; Ibrahim, Maryanne; Mayondi, Gloria; Leidner, Jean; Powis, Kathleen M; Cassidy, Adam R; Kammerer, Betsy; Ajibola, Gbolahan; Williams, Paige L; Weinberg, Adriana; et al.
Abstract: Background: We sought to identify predictors of child cytomegalovirus (CMV) infection overall and by maternal HIV status and to assess associations of child CMV status with growth and neurodevelopmental outcomes at 24 months of age in Botswana. Methods: Data and samples were used from the Botswana-based observational Tshipidi study (2010–2014), enrolling pregnant women living with and without HIV and following their infants through 2 years of age. Child plasma samples were tested at 18 months of age for anti-CMV immunoglobulin G (IgG). Associations were assessed between detectable anti-CMV IgG and growth (using the World Health Organization Child Growth Standards) and neurodevelopment (using the Bayley Scales of Infant and Toddler Development III and the Developmental Milestones Checklist) at 24 months of age. Results: Of 317 children, 215 (68%) had detectable anti-CMV IgG at 18 months of age. Comparatively, 83% (n = 178) of HIV-unexposed uninfected (HUU) children had positive CMV serology vs 47% (n = 139) of HIV-exposed uninfected (HEU) children ( P < .01); 100% of HUU vs 10.5% of HEU children breastfed. Child CMV infection was not associated with weight-for-age, weight-for-length, or length-for-age z-scores at 24 months. In HUU children, CMV infection was associated with smaller head circumference ( P < .01). No difference was observed by child CMV status in any neurodevelopmental domain at 24 months. Conclusions: We observed high CMV seropositivity in 18-month-old children in Botswana, with higher seropositivity among breastfed (HUU) children. Positive CMV serostatus was not associated with 24-month child growth or neurodevelopmental outcomes, with the exception of smaller head circumference among HUU CMV-positive children.